2017
DOI: 10.1038/s41598-017-06149-4
|View full text |Cite
|
Sign up to set email alerts
|

The aspirin metabolite salicylate inhibits lysine acetyltransferases and MUC1 induced epithelial to mesenchymal transition

Abstract: MUC1 is a transmembrane mucin that can promote cancer progression, and its upregulation correlates with a worse prognosis in colon cancer. We examined the effects of overexpression of MUC1 in colon cancer cells, finding that it induced epithelial to mesenchymal transition (EMT), including enhanced migration and invasion, and increased Akt phosphorylation. When the clones were treated with the aspirin metabolite salicylate, Akt phosphorylation was decreased and EMT inhibited. As the salicylate motif is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
3
17
0
Order By: Relevance
“…Therefore, it has been hypothesised that these effects are related to the inhibition of HATs (Table 2). In vitro tests confirmed that salicylate directly inhibited the activity of PCAF, TIP60, and MOF in PC-3 prostate cancer cells, probably by reversing the epithelial-mesenchymal transition [28]. It has been proven that the strategy of HAT blocking using bi-substrate inhibitors is a very effective way of obtaining high affinity and selectivity of action by bioactive compounds.…”
Section: Histone Acetyltransferasesmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, it has been hypothesised that these effects are related to the inhibition of HATs (Table 2). In vitro tests confirmed that salicylate directly inhibited the activity of PCAF, TIP60, and MOF in PC-3 prostate cancer cells, probably by reversing the epithelial-mesenchymal transition [28]. It has been proven that the strategy of HAT blocking using bi-substrate inhibitors is a very effective way of obtaining high affinity and selectivity of action by bioactive compounds.…”
Section: Histone Acetyltransferasesmentioning
confidence: 86%
“…Therefore, it has been hypothesised that these effects are related to the inhibition of HATs ( Table 2 ). In vitro tests confirmed that salicylate directly inhibited the activity of PCAF, TIP60, and MOF in PC-3 prostate cancer cells, probably by reversing the epithelial–mesenchymal transition [ 28 ].…”
Section: Histone Acetyltransferasesmentioning
confidence: 99%
“…The chemopreventive and anticarcinogenic activities of ASA have largely been attributed to COX inhibition resulting in reduced synthesis of PGE 2 , which is upregulated in cancers (3) and implicated in multiple carcinogenic processes (58). In addition, ASA has been shown to activate the ATM kinase (35) and block NFκB (36) and Akt pathways (37). Other activities of ASA include activation of AMPK (9) that may regulate mTOR pathways involved in autophagy (11) and apoptosis (10) in cancer cells, and inhibition of heparanase that was associated with reduced angiogenesis and growth of tumor xenografts (22).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive body of retrospective clinical evidence suggesting an association of aspirin with improved PrCa outcomes, very few preclinical studies examined the effects of aspirin in PrCa models and even fewer focused specifically on SAL. High dose SAL (0.5‐20 mM) was shown to suppress growth in PrCa cell models and block endothelial to mesenchymal transition (EMT) in PC3 cells . In cervical cancer SAL was shown to enhance the anti‐proliferative and pro‐apoptotic effects of RT but, to date, SAL has not been investigated in combination with RT in pre‐clinical models of PrCa.…”
Section: Discussionmentioning
confidence: 99%
“…High dose SAL (0.5-20 mM) was shown to suppress growth in PrCa cell models 35,36 and block endothelial to mesenchymal transition (EMT) in PC3 cells. 37 In cervical cancer SAL was shown to enhance the antiproliferative and pro-apoptotic effects of RT 38 but, to date, SAL has not been investigated in combination with RT in pre-clinical models of PrCa.…”
Section: Salicylate Inhibits De Novo Lipogenesis (Dnl) In Pc3 Cellsmentioning
confidence: 99%